Beyond Emerson and the "Field of Dreams": Another Look at Innovation and Marketing - Cahill, Dennis J. (Senate Hall, 2007)
This note explores a new paradigm for thinking of innovation and innovating behavior, claiming that the Emerson/Field of Dreams paradigm so often used as justification for producing new highly-engineered products is a cause of the high failure rate for new products and services.
Keywords: mousetrap|“marketing concept”|innovation|product development